Index to livestock literature on Nigeria - Sirak Teklu; International Livestock Centre for Africa (Addis Ababa, Ethiopia : Library and Documentation Services, International Livestock Centre for Africa, 1992)
The book is practically a list of Institutions and places that caters to the needs of African livestock researchers.
"ILCA-MP/NG-2066/92."
Includes index.
gp 21/01/2019
Loans
Keywords: Livestock; Microfiches